Patterns of Gen Z's leisure time behavior and their needs towards urban recreational parks: A review - Ghani, Nurfaezah; Mansor, Mazlina; Zakariya, Khalilah (2016)
A study on the lifestyle of contemporary youth is very important to the provision and design of recreational park. Gen Z is people who born between the mid of the 1990s through the late 2000s. The purpose of this study was based on a literature review in order to describe a conceptual framework on the lifestyle patterns of Gen Z (ages 13-23) in relation to their leisure time activities and their current needs. The review covers 40 studies from 2008 to 2016 from four fields: epidemiological studies, lifestyle pattern, leisure and recreation, landscape and environmental planning. Leisure time behaviour involves the different types of voluntary activity like physical, leisure and social activities. Spending leisure time in an outdoor environment gives a positive effect on health. The result obtained from the reviews reveal the needs of Gen Z according to Abraham Maslow’s theory of needs. Therefore, the criteria of space in a recreational park could be revealed for encouraging park use among Gen Z to fulfill the acquisition for a healthy lifestyle.